ASPECTS REGARDING THE PROCESS OF DEVELOPING THE COORDINATION CAPACITY IN THE CASE OF PRESCHOOL CHILDREN (AGED 5-6) - Grădinaru C.; Pantea C. (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2012)
The present paper aims to represent the evolution of the results obtained by pre-schoolers following the introduction of dynamic games in the classes which aim to develop the coordination capacity. The group of children which was the focus of this research for one scholastic year (2011-2012) was composed of 13 girls and 16 boys, aged 5-6, an age precursory to the optimal period of developing the coordination capacity; the children that were selected actively took part in the physical education classes twice a week. The experiment we have conducted results in the formulation of the following conclusions: all the tests conducted have registered an increase of the coordination capacity from one measurement to another, as a consequence to the activity undertaken with this purpose, during the entire scholastic year. The evolutions recorded are not spectacular, but they support the idea that through organised exercise and activities, both in the case of girls and boys, progress can be achieved and the subjects can develop their coordination capacity.